(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
The aim of this work is to test the effectiveness of new thermal insulation material formed from semi-spherical Perlite expanded particles for liquefied petroleum gas (LPG) tanks. Five different samples of semi-spherical particles of (68.8, 90.4, 300.5, 1211000, 1861000) *10-9 m diameter are used as a new thermal insulating material in this work. To simulate the LPG tank wall, a stainless-steel plate of a thickness (3mm) is coated with this material and subjected to a resistive type flat plate heater. The thermal insulation coating thickness was (0.5mm to 2mm). This plate is subjected to different power loads namely (650, 1260 W/m2). Results show that increasing the insulation expanded particle size increases the difference in temperatures on both sides of the insulation layer. The first three sizes of the insulation material reported a temperature difference at both sides of the coating layer is about 18 oC, while that for the fourth and fifth size are 20 oC and 25 oC respectively since larger expanded particles size has higher air content that enables them to reduce and delay heat transfer. The thermal conductivity of coated thermal insulation with large Perlite particle size is (0.25 W/m.K), while that for small size is (0.42 W/m.K). The previously reported thermal conductivity for Silica granules is less than 0.4 W/(m.K)for insulation thickness of (50 mm), while that for binderless cotton stalk fiberboard (BCSF) is ranged from 0.0585 to 0.0815 W/m K for board thickness 25mm. The indicated thermal conductivity for coconut husk and bagasse insulation boards is 0.046 and 0.068 W/mK for board thickness 25mm. So utilizing Perlite expanded particles as an insulation material is superior since it is a slim layer not exceeded 2 mm.